Positron emission tomography/computed tomography (PET/CT) and CT for N staging of non-small cell lung cancer - Sandra Vegar Zubović; Spomenka Kristić; Besima Hadžihasanović (Medicinski glasnik, 2017)
Aim: The aim of this study is to investigate the possibilities of non-invasive diagnostic imaging methods, positron emission tomography/computed tomography (PET/CT) and CT, in clinical N staging of non-small cell lung cancer (NSCLC). Methods: Retrospective clinical study included 50 patients with diagnosed NSCLC who have undergone PET/CT for the purpose of disease staging. The International association for the study of lung cancer (IASLC) nodal mapping system was used for analysis of nodal disease. Data regarding CT N-staging and PET/CT Nstaging were recorded. Two methods were compared using χ2 test and Spearman rank correlation coefficient. Results: Statistical analysis showed that although there were some differences in determining the N stage between CT and PET/CT, these methods were in significant correlation. CT and PET/CT findings established the same N stage in 74% of the patients. In five patients based on PET/CT findings the staging was changed from operable to inoperable, while in four patients staging was changed from inoperable to operable. Conclusion: PET/CT and CT are noninvasive methods that can be reliably used for N staging of NSCLC.
Keywords: pulmonary cancer; multimodal imaging; lymph nodes